1998
DOI: 10.1007/bf01287413
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrion as the structural basis of the formation of a cell-type-specific organelle inDictyostelium development

Abstract: Summary.The mitochondrion has been mainly given attention as a self-reproductive and respiratory organelle. We report here that the mitochondrion may participate in the formation of a cell-type-specific organelle, coupling with the Golgi complex. During the development of Dictyostelium discoideum, the two types of cells, i.e., the anterior prestalk cells and the posterior prcspore cells form a polarized cell mass. Prespore differentiation is characterized by the presence of unique vacuoles named PSVs (prespore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
2
19
1
Order By: Relevance
“…4B,D). We previously reported that somewhat similar mitochondrial transformation occurred in differentiating prespore cells just before PSV formation (Matsuyama and Maeda, 1998). Nontreated Ax-2 cells contained normal-shaped mitochondria with reticular cisternae and an electron-opaque matrix, as shown in Fig.…”
Section: Creation Of ρ ∆ Cellsmentioning
confidence: 87%
See 2 more Smart Citations
“…4B,D). We previously reported that somewhat similar mitochondrial transformation occurred in differentiating prespore cells just before PSV formation (Matsuyama and Maeda, 1998). Nontreated Ax-2 cells contained normal-shaped mitochondria with reticular cisternae and an electron-opaque matrix, as shown in Fig.…”
Section: Creation Of ρ ∆ Cellsmentioning
confidence: 87%
“…Journal of Cell Science 117 (15) In differentiating prespore cells, mitochondria exhibit a drastic structural transformation to form a sort of vacuole (Mvacuole), in which PSVs are constructed with the help of the Golgi complex (Maeda, 1971;Matsuyama and Maeda, 1998). Interestingly, during the formation of ρ ∆ cells mitochondria exhibit a marked morphological change and form unique vacuoles similar to the M-vacuole (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Dictyostelium, PSV (prespore-specific vacuole) has been shown to be formed by structural transformation of mitochondria [Matsuyama and Maeda, 1998]. Involvement of cyanide (CN)-resistant respiration in cell-type proportioning has also been indicated [Matsuyama and Maeda, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Dictyostelium have shown the Journal of Cell Science 119 (6) involvement of mitochondria in cell differentiation and pattern formation (Chida et al, 2004;Kotsifas et al, 2002;Matsuyama and Maeda, 1998;Wilczynska et al, 1997). Cells with reduced amount of mitochondrial DNA were obtained by exposing Dictyostelium cells to ethidium bromide (Chida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%